The Development Of The Islamic Social Enterprise Management Index (isemi) - Saunah Zainon; Rashidah Mokhtar; Kum Yoke Soo; Rahimah Mohamed Yunos; Nur Eyliawati Japelus; Nurul Huda Md Yatim; Muhammad Iqmal Hisham Kamruddin (Virtus Interpress, 2024)
Non-Indexed Publication